E-learning success factors : an academic perspective / Mohd Aliff Sarjani - Sarjani, Mohd Aliff (2006)
Globally, many institutions of higher learning have incorporated e-learning as part of their academic program. Malaysian institutions of higher learning have been slow in incorporating e-learning but today, this mode of learning and teaching that is supported by ICT is gaining increasing recognition with its flexibiUty and convenience especially among the ICT literate population. However, e-learning is still comparatively under utilized and not extensively being used in most local institutions of higher learning. This research was based on three perspectives: institution staff (institution), lecturer (instructor) and learner (student). The objectives of this research are to determine the success factors of e-learning, to assess the successfullnes of implementing e-learning in Malaysian Institutes of Higher Learning (IHL) which are based in Klang Valley region and to identify the impact of selected demographic characteristics toward successfiilness of implementing e-learning. The IHLs were registered with the Ministry of Higher Education and most of the institution had obtained Multimedia Super Corridor (MSC) status (with reference at www.msc.com.my).The research model that are used is based on the e-learning framework adapted by al-Rawas (2001) and improved by McPherson (2002). 500 questionnaires had been distributed among the 20 Malaysian IHLs, but only 14 IHLs had participated in the survey. The targeted respondents from institutions staff are 150, instmctor 150 and leamer 200. The actual respondent who participated in the surveys are 140 respondents from institutions staff, 145 respondents from instructor and 180 respondents from leamer. The findings indicated that the following success factors are successfully implemented in IHLs: enabling technology, organizational context, curriculum development, institutional design and delivery. Although there were limitations encountered during the research, however the research had completed successfully.